Synergistic and low adverse effect cancer immunotherapy by immunogenic chemotherapy and locally expressed PD-L1 trap - Wantong Song (Nature Portfolio, 2018)
Microsatellite-stable (MSS) colorectal cancer (CRC) has shown poor response to checkpoint blockade immunotherapy. Here, the authors show that the combination of oxaliplatin with anti-PDL1 mAb is specifically efficient in the treatment of MSS CRC.